Α‐L‐Fucosidase Inhibition by Pyrrolidine–Ferrocene Hybrids: Rationalization of Ligand‐Binding Properties by Structural Studies. Issue 29 (5th June 2013) - Hottin, Audrey; Wright, Daniel W.; Steenackers, Agata; Delannoy, Philippe; Dubar, Faustine; Biot, Christophe; Davies, Gideon J.; Behr, Jean‐Bernard
Abstract Enhanced metabolism of fucose through fucosidase overexpression is a signature of some cancer types, thus suggesting that fucosidase‐targetted ligands could play the role of drug‐delivery vectors. Herein, we describe the synthesis of a new series of pyrrolidine–ferrocene conjugates, consisting of a L‐fuco‐configured dihydroxypyrrolidine as the fucosidase ligand armed with a cytotoxic ferrocenylamine moeity. Three‐dimensional structures of several of these fucosidase inhibitors reveal transition‐state‐mimicking 3E conformations. Elaboration with the ferrocenyl moiety results in sub‐micromolar inhibitors of both bovine and bacterial fucosidases, with the 3D structure of the latter revealing electron density indicative of highly mobile alkylferrocene compounds. The best compounds show a strong antiproliferative effect, with up to 100 % inhibition of the proliferation of MDA‐MB‐231 cancer cells at 50 μM.